Evaluation of Nitric Oxide (NO) and Nitric Oxide Synthases (NOS) in the Amniotic Fluid in an Experimental Gastroschisis Rat Model - Gonçalves, F.L. L.; de Souza, G.F. P.; Schmidt, A. F.; Regis, A. C.; de Oliveira, M. G.; Sbragia, L. (European Journal of Pediatric Surgery, 2011)
Intestinal damage due to gastroschisis (G), an anomaly found with increasing incidence by pedriatic surgeons, is intimately associated with endogenous nitric oxide (NO) production and NO synthase (NOS) expression.Aim of the study was to evaluate NO production and NOS isoforms in the intestine and amniotic fluid (AF) using a rat model of gastroschisis.A gastroschisis rat model was surgically created at 18.5 days of gestation (term=22 days). 3 groups of 12 fetuses each were studied: control (C), sham (S) and (G). Morphometric data of body weight (BW), intestinal weight (IW) and the IW/BW ratio were evaluated and compared. Indirect quantification of NO (nitrite and nitrate – NOx) was analyzed by chemiluminescence, and the expression of the 3 isoforms was analyzed by Western blotting.Group G showed an increase in IW and IW/BW compared with groups C and S. IW: G=0.27±0.06, C=0.20±0.02, S=0.20±0.02 (p<0.01); IW/BW: G=4.11±0.57, C=5.21±1.04, S=5.18±1.23 (p<0.05). NO in the G group was lower in the intestine and higher in AF, as opposed to C and S, where it had increased in the intestine and decreased in AF. Intestinal NOx: G=0.85±0.28, C=1.86±0.82, S=1.80±0.69 (p<0.05); NOx in AF: G=161.87±52.11, C=6.99±5.45, S=48.73±13.183 (p<0.001).The intestinal inflammation in gastroschisis promotes the release of nitric oxide to the environment (AF). Perhaps NO in the AF may be an inflammatory marker for G.
Keywords: gastroschisis; nitric oxide synthases; experimental surgery; amniotic fluid